Learning Policy Analysis during the Covid-19 Pandemic: Between Opportunities and Challenges and Their Impact on Islamic Education - Ahmad Syarif; Imam Mawardi (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The impact of the corona virus outbreak 19, causing a global pandemic to occur in almost all parts of the world. This has an impact on the education system in Indonesia. Since the announcement of Distance Learning (PJJ) by the Central Ministry of Education and Culture, SMP Muhammadiyah 1 Pati has implemented an online learning policy for all students and teachers. This study intends to examine the analysis of learning policies during the Pandemic era at SMP Muhammadiyah 1 Pati. This research is a qualitative descriptive study. The data analysis technique used by the writer in this research is qualitative data analysis technique. The results of the author's research on the online learning management policy during the pandemic at SMP Muhammadiyah 1 Pati concluded that: 1) The effectiveness of learning management during a pandemic at SMP Muhammadiyah 1 Pati has been going well. However, it still requires development related to human resources in improving technological capabilities, as well as school readiness to provide Sarpras during online learning. 2) Opportunities that occur during online learning include teachers and students being more flexible in teaching and learning activities, the ability to interact with technology is increasing, and parents also take a direct role in the learning process. Besides, there are opportunities, there are also challenges, namely network limitations, lack of teacher training on contemporary learning media, and the economic conditions of each student which are the obstacles. Unavailability of Android phones. This is another problem in the application of online learning: 3) The impact of learning during a pandemic is twofold; The first is the positive impact, educators and students can easily make breakthroughs in online learning through online without any distance and boundaries. Besides the positive impacts, of course there are also negative impacts, among the negative impacts that accompany the pandemic situation on Islamic education are: the crisis morals and personality of the students.